Conflicting Digital Futures: An Analysis of the New Zealand Digital Television Debate in Relation to Public Service Principles and Commercial Imperatives - Brill, Yvonne Charlotte (Auckland University of Technology, 2012)
The freedom to provide a wide range of content from diverse sources allows the media to fulfil its role as facilitator of the public sphere. Having access to a wide range of content from diverse sources is necessary if citizens are to fully participate in the democratic process. However, provision of non-commercial and public service content has proved problematic in New Zealand’s deregulated broadcasting environment. During the 1980s and 1990s the international trend toward deregulated national media markets put public service media under considerable pressure. In a deregulated environment commercial interests flourished, often at the expense of the public interest. This was certainly the case with broadcasting. Since then, New Zealand’s television broadcasting market has struggled to provide a balance of commercial and non-commercial content for a variety of reasons. But the digital era of broadcasting brings with it new opportunities for public service broadcasting provision. A by-product of the government’s decision to begin the switchover from analogue to digital broadcasting was the establishment of two non-commercial digital channels, administered by state-owned broadcaster, TVNZ. However, less than five years after the digital initiatives were announced, both channels had ceased broadcasting and once again the market became dominated by commercial interests. This thesis begins with a political-economic overview of New Zealand broadcasting history. The latter part of the overview traces the emergence of the neoliberal orthodoxy which informed the radical deregulation of the broadcasting sector, as well as ‘Third Wayism,’ which entailed a partial recommitment to public service broadcasting. In this context, the establishment of the Freeview platform and TVNZ’s digital channels, as well as the subsequent demise of these channels are examined. These developments were reported in the mainstream media in certain ways. In this context I provide a case study of how public service broadcasting was framed in news coverage from 2006-2011. This makes it possible to evaluate the parameters of the debate concerning public service broadcasting in the digital era. My conclusion here is that the debate was framed in such a way that public broadcasting was made to appear as if it was an imposition on the taxpayer, and commercially driven broadcasting was positioned as the default.
Keywords: Public sphere; Digital broadcasting; Public service broadcasting; Neoliberalism; Third Way; Political economy; Frame analysis; Public service; Media framing; State ownership; Media ownership; Television; New Zealand; TVNZ charter; Broadcasting reforms; TVNZ 7; News frames; Non commercial broadcasting; Rogernomics; TVNZ 6